2013
DOI: 10.1002/jobm.201300250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacillus spp. strains on seedling growth and physiological parameters of sorghum under moisture stress conditions

Abstract: Microorganisms isolated from stressed ecosystem may prove as ideal candidates for development of bio-inoculants for stressed agricultural production systems. In the present study, moisture stress tolerant rhizobacteria were isolated from the rhizosphere of sorghum, pigeonpea, and cowpea grown under semiarid conditions in India. Four isolates KB122, KB129, KB133, and KB142 from sorghum rhizosphere exhibited plant growth promoting traits and tolerance to salinity, high temperature, and moisture stress. These iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 33 publications
5
36
0
2
Order By: Relevance
“…The plant shoot length was also increased. Increases in shoot and plant growth under drought stress as a result of PGPR treatment have also been reported in other crops including sorghum (Sorghum bicolor L.) (Grover et al, 2014), sunflower (Helianthus annuus L.) (Castillo et al, 2013), wheat (Arzanesh et al, 2011;Kasim et al, 2013), green gram (Vigna radiata L.) (Saravanakumar et al, 2011) mung bean (Vigna radiata L.) (Sarma and Saikia, 2014) and maize Naseem and Bano, 2014;Naveed et al, 2014) (Table 1). Taken together, the above studies clearly show that treatment of plants with selected strains of PGPR leads to increase in shoot growth and improvements in plant growth which help plants tolerate drought stress.…”
Section: Zea Mayssupporting
confidence: 54%
See 2 more Smart Citations
“…The plant shoot length was also increased. Increases in shoot and plant growth under drought stress as a result of PGPR treatment have also been reported in other crops including sorghum (Sorghum bicolor L.) (Grover et al, 2014), sunflower (Helianthus annuus L.) (Castillo et al, 2013), wheat (Arzanesh et al, 2011;Kasim et al, 2013), green gram (Vigna radiata L.) (Saravanakumar et al, 2011) mung bean (Vigna radiata L.) (Sarma and Saikia, 2014) and maize Naseem and Bano, 2014;Naveed et al, 2014) (Table 1). Taken together, the above studies clearly show that treatment of plants with selected strains of PGPR leads to increase in shoot growth and improvements in plant growth which help plants tolerate drought stress.…”
Section: Zea Mayssupporting
confidence: 54%
“…This has been demonstrated in maize Vardharajula et al, 2011;Naseem and Bano, 2014), sorghum (Grover et al, 2014), potato plants (Gururani et al, 2013), mung bean (Sarma and Saikia, 2014), and Arabidopsis (Arabidopsis thaliana L.) (Cohen et al, 2015) (Table 1). For example, Wang et al (2012) reported that treatment of cucumber (Cucumis sativa L.) plants with a mixture of three PGPR strains (Bacillus cereus AR156, Bacillus subtilis SM21, and Serratia sp.…”
Section: Osmotic Adjustment For Drought Tolerancementioning
confidence: 77%
See 1 more Smart Citation
“…The mechanism of Bacillus spp. inoculation promoting growth and enhancing biotic or abiotic stress tolerance has been reported in many crops via different mechanisms (Vardharajula et al 2011;Grover et al 2014). Hawkes et al (2008) explained that increasing plant growth may be due to enhanced nutrient transfer to the host plant or altered carbon allocation pattern from plant to mycorrhiza.…”
Section: Effects Of Inoculation With B Pumilus On Growth Parameters mentioning
confidence: 99%
“…Studies on plant growth promoting bacteria report a better use of water in inoculated plants, evidencing that the plant growth promoting bacteria help in the plant survival, because they maintain the highest relative water content (Grover et al 2014, Fan et al 2015. Accordingly, higher relative water content values represent plants with an advanced capacity of physiological adaptation to the environment, maintenance of cell division and physiological activity (Ngumbi & Kloepper 2016).…”
Section: Resultsmentioning
confidence: 99%